(untitled) (Medical Forum Monthly, 2020)
Objective: To find out the frequency of leucocytosis in acute ischemic stroke and its effect on short term morbidity. Study Design: Descriptive Cross-Sectional study. Place and Duration of Study: This study was conducted at the Department of Neurology, PGMI Lady Reading Hospital Peshawar for six months January, 2012 to July, 2012. Materials and Methods: Data was collected by non-probability consecutive sampling technique. 126 adult patients with ischemic stroke were included in the study. Full blood count was obtained for all patients on admission and possibility of infection ruled out with history and relevant clinical examination. Presence of disability was assessed using Modified Rankin Scale ( mRS). Results: A total number of 126 patients having ischemic stroke were included in this study. The mean age was 61.9 years. 114 (64.4%) were males. Leukocytosis was seen in 61(76.25%) of the patients with significant morbidity, whereas 19(23.75%) of patients with morbidity had no leukocytosis. In patients without any significant morbidity leukocytosis was seen in only 12(26.09%) of the patients. Conclusion: It is concluded from this study that early leukocytosis in ischemic stroke patients is associated with increase morbidity and can therefore be considered as a prognostic factor.